Experience of the Endoscopists Matters in Endoscopic Retrograde Cholangiopancreatography in Billroth II Gastrectomy Patients - ŞENTÜRK, HAKAN; Caglar, Erkan; Atasoy, Deniz; Tozlu, Mukaddes; Altinkaya, Engin; Dogan, Serkan; ŞENTÜRK, HAKAN (My University, 2020)
Background/Aims: Altered anatomy is a challenge in endoscopic retrograde cholangiopancreatography (ERCP) for patients with Billroth II anastomosis. In this study, we investigated the overall success and role of endoscopist experience.